2009
DOI: 10.1029/2008gl036935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the assimilation of ozone from the Tropospheric Emission Spectrometer on surface ozone across North America

Abstract: We examine the impact of assimilating ozone observations from the Tropospheric Emission Spectrometer (TES) on North American surface ozone abundances in the GEOS‐Chem model in August 2006. The assimilation reduces the negative bias in the modeled free tropospheric ozone, which enhances the ozone flux into the boundary layer. Surface ozone abundances increased by as much as 9 ppb in western North America and by less than 2 ppb in the southeast, resulting in a total background source of ozone of 20–40 ppb. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…We sum these three components to determine CO 2 . AM2 has not been used extensively in tracer transport studies (Parrington et al, 2009). To evaluate its performance, we compare CO 2 fields from AM2 with CO 2 generated with the TM5 tracer transport model underlying CarbonTracker using identical fluxes.…”
Section: Methodsmentioning
confidence: 99%
“…We sum these three components to determine CO 2 . AM2 has not been used extensively in tracer transport studies (Parrington et al, 2009). To evaluate its performance, we compare CO 2 fields from AM2 with CO 2 generated with the TM5 tracer transport model underlying CarbonTracker using identical fluxes.…”
Section: Methodsmentioning
confidence: 99%
“…VOCs). Parrington et al (2009) demonstrated that the changes in the O 3 flux from the free troposphere into the planetary boundary layer (PBL) by the TES O 3 assimilation reduces the positive bias in the PBL indirectly over North America. Although this effect is not confirmed by our global analysis, it is of interest to survey the detailed spatial distributions resulting from the data assimilation.…”
Section: Comparison With Satellite Datamentioning
confidence: 99%
“…Suboptimal Kalman filters have been employed successfully for chemical data assimilation Lamarque et al, 2002;Segers et al, 2005;Clark et al, 2006;Pierce et al, 2007;Parrington et al, 2009). The use of the ensemble Kalman filter (EnKF) in chemical data assimilation has been studied in Constantinescu et al (2007b,c,d).…”
Section: Introductionmentioning
confidence: 99%